BIOPRODUCTS PRODUCTION FROM VEGETABLE OIL RESIDUAL: CANDLE, CHALK AND MODELLING OF MASS - Thode Filho, Sérgio; Sena, Marcelo Fonseca Monteiro de; Paixão, Cintia Patrícia Santos da; Maranhão, Fabíola da Silveira; Silva, Elmo Rodrigues da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Vegetable oils are widely used by the Brazilian population, whether domestic, commercial or industrial level. At the end of processing, the remaining oil is discarded, often incorrectly, or being released in effluents directly into the soil, making it a potentially polluting waste. The objective of this work is to obtain two alternative bioproducts such as mitigating the environmental impact caused by the improper disposal of waste vegetable oil. The processing starts with the dissolution of the solid soap in water in beaker and homogenized for 10 minutes to form a semisolid paste. Then was added 10g of residual charcoal powder, coal, granite, marble and/or other rocks, homogenizing for 3 minutes. The result of the processing described in the methods is a semi-solid paste, sandy exfoliating action and physical characteristic when used residual powder of marble and/or granite. When used residual charcoal powder, the result is a dark color and abrasive action. This work showed the possibility of obtaining two bioproducts as alternatives to mitigate the environmental impact caused by improper disposal of waste vegetable oil. The raw materials not expensive simplified procedures and routine equipment positively stimulate their production.